1912
DOI: 10.1037/h0075624
|View full text |Cite
|
Sign up to set email alerts
|

A tentative revision and extension of the Binet-Simon measuring scale of Intelligence.

Abstract: OLUME 111 FEBRUARY, 1912 NUMBER 2 'Age here means age at last birthday, (. r., 4 years includes children between 4 and r>. etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1916
1916
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…Also, some sources were not based on a sample sufficiently representative to be considered reasonably normative. Notable exclusions were Russell's (1975Russell's ( , 1988 revision of the WMS, the Stanford-Binet (S-B) intelligence batteries (Terman, 1917;Terman & Childs, 1912), as well as Starr (1924), Brener (1940) and Elwood (2001). Thus, based on the information included in Table 1, it can be seen that there were 10 normative sample sources included in this investigation across 85 years (1923 to 2008).…”
Section: Samples and Measurementioning
confidence: 99%
“…Also, some sources were not based on a sample sufficiently representative to be considered reasonably normative. Notable exclusions were Russell's (1975Russell's ( , 1988 revision of the WMS, the Stanford-Binet (S-B) intelligence batteries (Terman, 1917;Terman & Childs, 1912), as well as Starr (1924), Brener (1940) and Elwood (2001). Thus, based on the information included in Table 1, it can be seen that there were 10 normative sample sources included in this investigation across 85 years (1923 to 2008).…”
Section: Samples and Measurementioning
confidence: 99%
“…THE value of a qualitative analysis of the vocabulary definitions of children of different ages was recognised by Terman and Childs (1912), Terman (1916) and Pintner et a/. (1 944).…”
Section: Introductionmentioning
confidence: 99%
“…As in Feifel and Lorge's study, there was no evidence of a sex difference in level of definition at any age. Terman (1918) and Wechsler (1958) both acknowledged the criticism that vocabulary is necessarily influenced by educational and cultural opportunities, though Wechsler pointed out that a subject's cultural milieu is more likely to be revealed in quality of definition or knowledge of particular words than in total number of words known. Spache (1943) found that the Binet Vocabulary scores of children in private American schools tended to be in advance of these children's mental ages on the Stanford-Binet.…”
Section: Introductionmentioning
confidence: 99%
“…Sampling carefully from the kinds of activities deemed necessary for adequate performance in school, Binet developed age norms for these tasks and created the "intelligence" test.27 Henry H. Goddard published the first English language version,28 but the most influential translation was presented by Lewis M. Terman and H. G. Childs in 1912. 29 This was quickly adopted into the North American context eventuating in the 1916 Stanford-Binet Test of Intelligen~e.~'…”
mentioning
confidence: 99%